The Old Norse Poetic Meter Kviðuháttr as a Medium for History's Verdict. - Sayers, William (Amsterdamer Beiträge zur Älteren Germanistik, 2023)
The name of the Old Norse poetic meter kviðuháttr , as employed in historical poems such as Ynglingatal , is generally understood as meaning 'song' or 'poem meter'. Rather than accepting this designation at face value, the article hypothesizes an original * kviðsháttr or 'verdict meter' (< kviðr 'verdict, judicial judgment'), which was subsequently the object of folk etymologizing. This revised explanation illuminates the nature and objectives of not only Ynglingatal but also commemorative poems by Egill Skallagrímsson such as Sonatorrek and Arinbjarnarkviða.